Analytical reading of Executive Decree Num° 18/199 relating to the delegation of public service - Loucif, Nawel (Journal of Human Sciences, 2021)
The public service is a judicial theory, one of the theories of French administrative jurisprudence, which has received a great deal of attention from legal scholars, and given its importance and considered it as a strategic tool of governments , the Algerian legislator established regulations and a legal framework in 2015 by presidential decree 15/247, relating to public contracts and public utility authorizations, after he concluded the public service delegation agreements by executive decree no. ° 18/199 relating to the delegation of public service, which has become the source and the basis of any agreement concluded within the framework of the delegation of public service operation.